Mediation between tourism demand and cultural tourism marketing satisfaction in the twin cities of the Thai-Lao Mekong River - Sihabutr, Chaturaporn; Wuttipan, Cheewanan; Onpium, Pintusorn; Nonthapot, Sakkarin (International Journal of Innovative Research and Scientific Studies, 2025)
Thai and Chinese tourists are the main groups of tourists along the Thai-Lao Mekong River cultural tourism route. The purpose of this study is to examine the mediating effect of a mediator variable between tourism demand and satisfaction in cultural tourism marketing, using the concept of the 7Ps marketing mix. A total of 400 samples were collected through a convenient sampling method. The data were analyzed using the Partial Least Squares - Structural Equation Model (PLS-SEM). The estimation was conducted using the WarpPLS software, and the mediating effect variable test was performed with the Sobel Test. The results confirmed that the perception of value among tourists is the mediating factor between tourism demand and satisfaction with cultural tourism market factors. Therefore, related organizations should create tourism demand and enhance awareness of the value of cultural tourism destinations by organizing activities or programs suitable for the target groups to meet their needs in the tourism market.